Survei Kondisi Fisik Atlet Pencak Silat Persaudaraan Setia Hati Terate - Arifin, Agus Zaenal; Amiq, Fahrial; Fitriady, Gema (Sport Science and Health, 2020)
This study aims to determine the physical condition of the athletes of the UKM PSHT UM pencak silat. The physical components measured were arm muscle strength, abdominal muscle strength, leg muscle strength, agility, and cardiovascular endurance. The research method used is descriptive quantitative research method with survey technique design. The subjects in this study were 27 athletes of the UKM PSHT UM pencak silat, consisting of 21 male athletes and 6 female athletes. The results of the physical condition of the male athletes obtained arm muscle strength in the "moderate" category of the pull test, the "moderate" category of the push test. The average abdominal muscle strength was in the "Fair" category. The muscle strength of the legs averaged the â€œFairâ€ category. Agility is â€œAverageâ€ category average. Heart-lung endurance averaged in the â€œFairâ€ category. The physical condition of female athletes obtained the average arm muscle strength results in the "moderate" category, the average push test was in the "moderate" category. "Moderate" category average abdominal muscle strength. The muscle strength of the legs averaged the â€œFairâ€ category. â€œBelow averageâ€ category average agility. Heart-lung endurance averaged in the "Moderate" category. Based on the research results, it can be concluded that the physical condition of the athletes of UKM PSHT UM is not in the good or excellent category.Â Penelitian ini bertujuan untuk mengetahui kondisi fisik atlet pencak silat UKM PSHT UM. Komponen fisik yang diukur adalah kekuatan otot lengan, kekuatan otot perut, kekuatan otot tungkai, kelincahan, dan daya tahan jantung paru. Metode penelitian yang digunakan adalah metode penelitian deskriptif kuantitatif dengan rancangan teknik survei. Subjek dalam penelitian ini adalah atlet pencak silat UKM PSHT UM yang berjumlah 27 atlet, terdiri dari 21 atlet laki-laki dan 6 atlet perempuan. Hasil kondisi fisik atlet laki-laki memperoleh kekuatan otot lengan tes pull kategori â€œSedangâ€, tes push kategori â€œSedangâ€. Kekuatan otot perut rata-rata kategori â€œCukupâ€. Kekutan otot tungkai rata-rata kategori â€œCukupâ€. Kelincahan rata-rata kategori â€œRata-rataâ€. Daya tahan jantung paru rata-rata kategori â€œCukupâ€. Kondisi fisik atlet perempuan memperoleh hasil kekuatan otot lengan tes pull rata-rata masuk kategori â€œSedangâ€, tes push rata-rata kategori â€œSedangâ€. Kekuatan otot perut rata-rata kategori â€œSedangâ€. Kekutan otot tungkai rata-rata kategori â€œCukupâ€. Kelincahan rata-rata kategori â€œDi bawah rata-rataâ€. Daya tahan jantung paru rata-rata kategori â€œSedangâ€. Berdasarkan hasil penelitian dapat disimpulkan bahwa kondisi fisik atlet UKM PSHT UM tidak ada yang masuk kategori baik atau excellent.